Quantification of sludge from decanters: a case study carried out at the Seminary Water Treatment Plant in Mariana/MG (Research, Society and Development, 2022)
The objective was to quantify the production of solids in the ETA Seminar decanter, located in Mariana/MG. Equations from the literature were used to estimate production, which were modeled with parameters of the station under study. The equations used showed efficient quantification, with about 54 tons of produced sludge presented in the form of solids. The estimate of sludge production allows the station to implement the appropriate technique to dispose of waste and studies related to the correct disposal of this waste are expected, following the current environmental legislation.